The influence of strength level on sport-specific skills between stronger and weaker professional handball players - Kyriacou-Rossi, A.; Hadjicharalambous, M.; Zaras, N. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Handball is a complex team-sport that requires high-level of physical abilities and sport-specific skills in order to attain success [1]. Handball players spend a large part of their training in resistance training programs in order to enhance strength-power and as a consequence performance in the field [2]. However, the role of muscle strength on handball specific skills and whether stronger players may have a greater performance compared to weaker players remains largely unclear. The purpose of the study was to investigate the influence of muscle strength on handball specific skills and to examine the correlation between strength and handball specific skills.